Linking User Stories to UX elements: Recommendations to Reduce the Virtual Navigational Distances - Cleto Filho, Abner (2020)
Agile practices are approaches widely used in industrial context. User Stories (US) are valuable artifacts to agile teams, being a succinct description of a requirement with its details complemented by other artifacts. User eXperience (UX) is an important crosscutting quality requirement that has gained spotlight over the past years. Regarding the software development teams structure, the usage of teams that are not co-located is also a practice that has been utilized over the years, gaining more adepts over the years. Remote working has challenges reported in the literature, be it the time lapse among the team members, difficult on communication when compared to a face-to-face approach, and others. The usage of virtual environments and artifact-based communication are encouraged in the literature, given such are common to all team members, whether they are co-located or not. Many approaches on merging agile and UX are presented in the literature, but many issues are still faced in such enterprise. Problems on communication among UX specialists and agile developers, loss of big-picture, information traceability, and others, are recurring in the literature. Studies encourage the usage of artifacts to mediate communication, as well as to hold and share information, but few have analysed how UX information and USs are related in agile virtual environments. This master project presents an investigation on the navigational distances between UX information and USs in virtual environments. The investigation was performed through a case study in a software company and a qualitative analysis on the data collected. The investigation had the goal to understand how agile practitioners related UX information to USs. To do this, we conducted a qualitative analysis in 13 requirement documents of three different industry projects and we also explored the USs derived from such documents. Using the case study outcomes, we compare the issues found in it with the the literature. We identify the ways the artifacts can be related in the virtual environments, describing and providing pros and cons for each connection type. We propose a classification for navigational distances found among UX information and USs. Moreover, we propose a category on the navigational effort required to perform the navigation in virtual environments. The navigation and effort categories proposed extend the work of Bjarnason et al. (2016) on regards to navigational distance, considering it in virtual environments. Our work also contributes to motivate agile teams in rethinking about different forms to organize the UX information in virtual environments. We propose an arrangement template considering virtual environments, where the template displays a way to create USs and link it with UX elements, considering the navigational distance and effort classifications previously mentioned along with the goal to reduce the final navigational distance present among UX information and USs.